PEMBELAJARAN MENGIDENTIFIKASI MAKNA DALAM TEKS HIKAYAT DI KELAS X SMA - Aurel L Magfira; Idawati Garim (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Learning Meaning Learning in Tale Texts in Class X SMA. The purpose of this study was to implement learning to identify meaning in saga texts carried out by teachers and students in class X IPA 1 SMA Negeri 1 Toraja Utara. This study used descriptive qualitative method. The data used are learning data by teachers, data on the implementation of learning by teachers and students, learning the meaning of saga texts by students. Data collection techniques in this study were carried out through three steps, namely documentation, observation, and interviews. The results showed that the implementation of learning to identify meaning in saga texts was carried out by: (1) preparing a Lesson Plan, and (2) the teacher using authentic assessment techniques, namely the assessment used to assess the domains of attitudes, knowledge, and skills.